2013
DOI: 10.1016/j.biortech.2012.11.131
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between sequential and simultaneous application of activated carbon with membrane bioreactor for trace organic contaminant removal

Abstract: The removal efficiency of 22 selected trace organic contaminants by sequential application of granular activated carbon (GAC) and simultaneous application of powdered activated carbon (PAC) with membrane bioreactor (MBR) was compared in this study. Both sequential application of GAC following MBR treatment (MBR-GAC) and simultaneous application of PAC within MBR (PAC-MBR) achieved improved removal (over 95%) of seven hydrophilic and biologically persistent compounds, which were less efficiently removed by MBR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 17 publications
0
16
0
1
Order By: Relevance
“…They reported that adsorption onto activated carbon improved the overall removal of CBZ by as much as 40% [203]. Nguyen et al [210] also reported an overall CBZ removal of 98% by an MBR followed by GAC adsorption. When a sequencing batch reactor coupled to an external microfiltration membrane was investigated by Serrano et al [241], up to 93% CBZ removal was achieved following the addition of a single dose (1 g/L) of PAC directly into the bioreactor.…”
Section: Combined/hybrid Treatment Systemsmentioning
confidence: 98%
See 2 more Smart Citations
“…They reported that adsorption onto activated carbon improved the overall removal of CBZ by as much as 40% [203]. Nguyen et al [210] also reported an overall CBZ removal of 98% by an MBR followed by GAC adsorption. When a sequencing batch reactor coupled to an external microfiltration membrane was investigated by Serrano et al [241], up to 93% CBZ removal was achieved following the addition of a single dose (1 g/L) of PAC directly into the bioreactor.…”
Section: Combined/hybrid Treatment Systemsmentioning
confidence: 98%
“…CBZ removal by MBR treatment followed by GAC filtration was investigated by Nguyen et al [210]. While MBR alone showed a removal of less than 20%, MBR-GAC achieved an extremely efficient removal of 98% [210]. This result demonstrates that GAC post-treatment could significantly improve the removal of PhACs, which are resistant to degradation by the activated sludge.…”
Section: Combined/hybrid Treatment Systemsmentioning
confidence: 98%
See 1 more Smart Citation
“…It can also be used to mitigate membrane fouling (in MBRs) and facilitate the removal of TrOCs from the aqueous phase through sorption [86][87][88][89][90][91].…”
Section: Addition Of Sorbent Materialsmentioning
confidence: 99%
“…While the sorption of TrOCs on sorbents such as powdered and granular activated carbon (PAC and GAC, respectively) can help improve effluent quality, the conceptual expectation of 'bioregeneration' of the sorbents is often not accomplished [86][87][88][89], consequently necessitating periodic withdrawal of the spent adsorbent and its replenishment. The withdrawn sludge contains high concentrations of resistant TrOCs and needs to be properly treated and disposed.…”
Section: Addition Of Sorbent Materialsmentioning
confidence: 99%